1996
DOI: 10.1111/j.1476-5381.1996.tb15186.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of tert‐butyl‐benzohydroquinone, a putative SR Ca2+ pump inhibitor, on isometric relaxation during the staircase in the rabbit and rat ventricle

Abstract: 1 The effects of 2,5 di-(tert-butyl)-1,4-benzohydroquinone (TBQ), a putative inhibitor of the sarcoplasmic reticulum Ca21 pump, on mechanical relaxation and contraction-relaxation coupling have been studied at different frequencies (0.5-3 Hz) in isometrically contracting isolated right ventricular preparations of rabbit and rat at 370C. Two types of mechanical responses have been studied: the twitch tension and the force transient (rewarming spike, RSp) following a rapid cooling contracture (RCC, an index of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Finally, the coupling between inotropism and relaxation (Chemla et al, 1986) has led us to analyse more precisely the part taken by the SR Ca2+ pump and the Na+/Ca2+ exchanger in Ca2+ reduction. This, and a possible 'intrinsic' relaxant effect (Chemla et al, 1986) of TBQ, are reported in the companion paper (Baudet et al, 1996).…”
Section: Ca2mentioning
confidence: 64%
“…Finally, the coupling between inotropism and relaxation (Chemla et al, 1986) has led us to analyse more precisely the part taken by the SR Ca2+ pump and the Na+/Ca2+ exchanger in Ca2+ reduction. This, and a possible 'intrinsic' relaxant effect (Chemla et al, 1986) of TBQ, are reported in the companion paper (Baudet et al, 1996).…”
Section: Ca2mentioning
confidence: 64%